Metode Simple Multi-Attribute Rating Technique untuk Pengambilan Keputusan Seleksi Karyawan PT. PSMI - Dika Hastanto; Dian Resha Agustina; Dwi Romadhan; Leni Septiani (LPPM STT Terpadu Nurul Fikri, 2025)
The employee selection process at PT PSMI has been considered less optimal due to limitations in objectively assessing candidates and indications of subjectivity from the Human Resource Development (HRD) department. This condition may prevent the company from obtaining candidates who truly meet organizational requirements. This study aims to address these issues by applying the Simple Multi-Attribute Rating Technique (SMART) method within a decision support system (DSS) for employee selection. The SMART method assists decision-making based on five main criteria: education, work experience, age, test scores, and interview results. Research data were collected through interviews and questionnaires with the HRD department to determine the weight of each criterion according to its level of importance. Candidate scores were then analyzed using the SMART calculation stages to obtain the final scores and determine the best ranking. The evaluation results show that candidate A07 achieved the highest score of 90.63 and was recommended as the best prospective employee. Validation was carried out by comparing the system results with HRD decisions, showing a high level of consistency. These findings demonstrate that the SMART method effectively enhances objectivity, reduces subjectivity, and accelerates the employee selection process at PT PSMI. The results of this study are expected to serve as a reference for other companies in developing decision support systems based on the SMART method to achieve a more objective recruitment process.